A low-detection-limit nitrogen dioxide gas sensor based on core-shell Pd@Pt nanocrystal modified ZnO and a preparation method thereof
Patent Information
- Application Number
- CN202311301885.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-10-10
AI Technical Summary
然而,利用Pd@Pt核壳纳米晶体修饰MOS气体传感器的研究仍处于空白阶段
[0016]1.利用简单的水浴法和共还原法就可以制备ZnO纳米片与核壳结构双金属Pd@Pt纳米晶体两种材料,并通过混合搅拌获得基于核壳结构双金属Pd@Pt纳米晶体修饰的ZnO敏感材料,这种合成方法简单,成本低廉;
Smart Images

Figure CN117347442B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor oxide gas sensor technology, specifically relating to a low detection limit nitrogen dioxide gas sensor based on core-shell bimetallic Pd@Pt nanocrystals modified with ZnO and its preparation method. Background Technology
[0002] Over the past few decades, the rapid expansion of industrial activities and transportation infrastructure has led to a significant increase in the emission of harmful gases into the Earth's atmosphere. Long-term exposure to air pollution caused by toxic and harmful gases can damage the human brain and impair cognitive abilities. Nitrogen dioxide, as one of the common toxic and harmful gases, not only causes problems such as acid rain and ozone, but also causes serious diseases such as lung damage, respiratory infections, and airway inflammation. The World Health Organization (WHO) recommends an annual average NO2 concentration standard of 40 μg / m³ for ambient air quality. -3 (Equivalent to 21.25 ppb). Furthermore, nitrogen dioxide can serve as a biomarker in diagnostic processes, particularly at levels of parts per billion (ppb) or parts per trillion (ppt), for diagnosing diseases such as lung infections and gastrointestinal disturbances. Therefore, developing a gas sensor with high sensitivity and good selectivity for ppb-level NO2 is crucial.
[0003] Metal-oxide-semiconductor (MOS) gas sensors have attracted increasing attention and research due to their advantages such as low cost, ease of operation, miniaturization, and ease of integration. Although significant progress has been made in MOS-based nitrogen dioxide gas sensors, some shortcomings remain, such as high operating temperature, long response recovery time, low sensitivity, and poor selectivity. The main reason for these problems is the limited surface area of the MOS covering the gas sensor, resulting in insufficient exposed active sites, leading to weak gas molecule absorption and poor electron transport. These problems are difficult to solve simply by adjusting the morphology and structure of the MOS.
[0004] Noble metal modification is an effective way to improve the sensitivity, reduce operating temperature, enhance selectivity, and lower the detection limit of MOS materials. The significant improvement in gas sensing performance is mainly due to the chemical and electronic sensitization brought about by noble metals. Compared with single metals, bimetallic nanoparticles generally exhibit better catalytic activity, thanks to the enhancement or synergistic effect produced by the electronic coupling between the two metals. Theoretical calculations show that orbital hybridization between different atoms in bimetallic nanocrystals generates new energy levels, which in turn allows more gas molecules to participate in the surface redox reactions of the sensing material. The pairing of palladium and platinum is particularly interesting because they have the smallest lattice mismatch (only 0.77%), allowing for the formation of a core-shell structure. Furthermore, the strong interaction between Pd and Pt can produce a synergistic effect, further enhancing catalytic activity. In recent years, many studies have focused on using Pd@Pt alloy nanocrystals to modify MOS materials to improve gas sensing performance. However, research on modifying MOS gas sensors using Pd@Pt core-shell nanocrystals remains in its infancy. Summary of the Invention
[0005] The purpose of this invention is to provide a nitrogen dioxide gas sensor with a low detection limit based on core-shell bimetallic Pd@Pt nanocrystals modified with ZnO and its preparation method.
[0006] This invention modifies the surface of a traditional gas sensing metal semiconductor oxide, enabling the detection of low concentrations of nitrogen dioxide gas with good selectivity.
[0007] The present invention discloses a nitrogen dioxide gas sensor based on core-shell bimetallic Pd@Pt nanocrystal-modified ZnO, comprising an alumina ceramic tube substrate with two annular gold electrodes on its outer surface, a sensitive material coated on the gold electrodes and the outer surface of the alumina ceramic tube, and a nickel-chromium heating wire located inside the alumina ceramic tube substrate. The sensor is characterized in that the sensitive material is core-shell bimetallic Pd@Pt nanocrystal-modified ZnO, and it is prepared by the following steps.
[0008] (1) Dissolve 5.8-6.2g of zinc nitrate hexahydrate and 0.16-0.18g of sodium dodecylbenzenesulfonate in 30-50mL of deionized water and stir thoroughly until dissolved to obtain solution A; then dissolve 2.2-2.6g of sodium hydroxide in 10-20mL of deionized water, add the obtained sodium hydroxide aqueous solution dropwise to solution A and stir for 20-40min; transfer the resulting mixture to an autoclave and heat at 80-100℃ for 1.5-2.5 hours; after naturally cooling to room temperature, wash the obtained precipitate by centrifugation with deionized water and ethanol 3-6 times in sequence and collect it; dry the obtained product at 50-70℃ overnight, and then calcine at 350-450℃ for 0.5-2.0 hours to obtain ZnO nanosheets;
[0009] (2) Dissolve 40-60 mg of polyvinylpyrrolidone, 40-60 mg of ascorbic acid, 0.05-0.15 mmol of sodium tetrachloropalladium and 0.05-0.15 mmol of platinum acetylacetonate in 8-12 mL of ethylene glycol, stir thoroughly until completely dissolved, and then heat in an oil bath to 160-200 °C and maintain for 2-5 hours; after cooling to room temperature, wash the obtained precipitate by centrifugation with acetone and ethanol 3-6 times in sequence and collect it. Disperse the obtained product in ethanol to obtain a bimetallic Pd@Pt nanocrystal ethanol dispersion;
[0010] (3) 100 mg of ZnO nanosheets obtained in step (1) were ultrasonically dispersed in 8-12 mL of ethanol, and the ethanol dispersion of Pd@Pt nanocrystals obtained in step (2) was added to it. The mixture was stirred for 20-40 minutes. The amount of bimetallic Pd@Pt nanocrystals was 0.1-0.5% of the mass of ZnO nanosheets. Finally, the mixture was dried overnight at 50-70 °C to obtain a core-shell structured bimetallic Pd@Pt nanocrystal modified ZnO sensitive material.
[0011] The ZnO sensing material has the morphology of nanosheets, while the core-shell bimetallic Pd@Pt nanocrystals are modified on the surface of the ZnO nanosheets. The size of the Pd@Pt nanocrystals is about 6 nm. Since Pd@Pt and ZnO have different work functions, electron transfer occurs between them, forming a Schottky barrier. The presence of the Schottky barrier will widen the depletion layer and increase the baseline resistance, which is beneficial to improving the sensor's response to gases.
[0012] The present invention discloses a method for preparing a low detection limit nitrogen dioxide gas sensor based on core-shell bimetallic Pd@Pt nanocrystals modified with ZnO, the steps of which are as follows:
[0013] ① Mix 10-20 mg of core-shell bimetallic Pd@Pt nanocrystal-modified ZnO sensitive material with 1-3 mL of ethanol in a mortar until homogeneous. Then, use a small brush to evenly coat the resulting mixture onto the outer surface of an alumina ceramic tube with a length of 3.5-4.5 mm, an outer diameter of 1.1-1.3 mm, and an inner diameter of 0.7-0.9 mm, and cover it with a gold electrode to form a sensitive material film with a thickness of 12-16 μm. Then, bake it under an infrared lamp for 8-15 minutes. After the ethanol evaporates, sinter the alumina ceramic tube at 250-350℃ for 1.5-3.0 h to improve the mechanical strength of the sensitive material.
[0014] ② The sintered alumina ceramic tube is welded onto a hexagonal base, and a nickel-chromium heating wire is inserted inside the alumina ceramic tube as a heater to control the working temperature of the sensor. The tube is aged at 180-220°C for 3-6 days to obtain the low detection limit nitrogen dioxide sensor based on core-shell bimetallic Pd@Pt nanocrystal modified ZnO as described in this invention.
[0015] The low-detection-limit nitrogen dioxide gas sensor with core-shell structured bimetallic Pd@Pt nanocrystals modified with ZnO prepared in this invention has the following advantages:
[0016] 1. Two materials, ZnO nanosheets and core-shell bimetallic Pd@Pt nanocrystals, can be prepared using a simple water bath method and a co-reduction method. By mixing and stirring, ZnO-sensitive materials modified with core-shell bimetallic Pd@Pt nanocrystals can be obtained. This synthesis method is simple and low in cost.
[0017] 2. ZnO has a nanosheet structure, and its large specific surface area provides more reaction sites. Due to the sensitizing and synergistic effects of bimetals, its excellent catalytic activity promotes the reaction. Better gas-sensing performance can be obtained with a smaller bimetal loading, which is beneficial to improving catalyst utilization and reducing costs.
[0018] 3. It adopts commercially available tubular sensors, which have simple manufacturing processes, small size, and are suitable for mass production. Attached Figure Description
[0019] Figure 1 (a) is a TEM image of Pd@Pt nanocrystals; (b) is a high-resolution TEM image of Pd@Pt nanocrystals; (c) is a frequency distribution histogram of Pd@Pt nanocrystals; (d) and (e) are line scan images of Pd@Pt nanocrystals.
[0020] like Figure 1 As shown in (a), the Pd@Pt nanocrystals are uniformly dispersed without agglomeration. Figure 1 As shown in (c), the diameter of the Pd@Pt nanocrystals is 5.5–6.5 nm. Figure 1 As shown in (b), the lattice fringes at the edge of the nanocrystal, approximately 0.226 nm, correspond to the (111) plane of Pt, confirming the formation of the Pt shell. Meanwhile, the lattice fringes at the center of the nanocrystal, approximately 0.224 nm, correspond to the (111) plane of PdPt. Figure 1 As shown in (d) and 1(e), the line scan diagrams show that the diffraction peak intensity of Pt at the edge of the nanocrystal is significantly higher than that of Pd, while the diffraction peak intensity of Pd in the central region is significantly higher than that of Pt, proving the formation of the core-shell structure of the nanocrystal.
[0021] Figure 2 (a) is a SEM image of 0.3wt% Pd@Pt-ZnO; (b) and (c) are TEM images of 0.3wt% Pd@Pt-ZnO at different magnifications; (d) is a high-resolution TEM image of 0.3wt% Pd@Pt-ZnO.
[0022] like Figure 2As shown in (a) and (b), ZnO has a nanosheet structure. Figure 2 As shown in (c) and (d), the lattice spacing indicates that Pd@Pt nanocrystals were successfully supported on ZnO.
[0023] Figure 3 XRD patterns of ZnO, 0.3wt% Pd-ZnO, 0.3wt% Pt-ZnO, 0.1wt% Pd@Pt-ZnO, 0.3wt% Pd@Pt-ZnO and 0.5wt% Pd@Pt-ZnO composites in the range of 20° to 80°, and XRD standard card patterns of ZnO materials.
[0024] like Figure 3 As shown, the diffraction peaks of all samples correspond to the standard card PDF 36-1451, proving that the synthesized ZnO samples have high purity. However, no diffraction peaks corresponding to Pd or Pt appeared in the Pd@Pt-ZnO composite material. This should be due to the small particle size of Pd, Pt, and Pd@Pt nanocrystals and insufficient loading.
[0025] Figure 4 Operating temperature-sensitivity curves for ZnO, 0.3wt% Pd-ZnO, 0.3wt% Pt-ZnO, 0.1wt% Pd@Pt-ZnO, 0.3wt% Pd@Pt-ZnO, and 0.5wt% Pd@Pt-ZnO sensors.
[0026] The sensitivity is defined as: Sensitivity = Resistance between two gold electrodes in nitrogen dioxide / Resistance between two gold electrodes in air;
[0027] like Figure 4 As shown, all sensors exhibited gas sensitivity responses to 50 ppb nitrogen dioxide at temperatures ranging from 60 to 110 °C. It can be observed that the response initially increases with increasing temperature, then gradually decreases. The ZnO loaded with 0.3 wt% Pd@Pt showed a response as high as 60.3 at 80 °C, which is 21.16 times that of pure ZnO. The synergistic effect of Pd@Pt nanocrystals can improve gas sensitivity. Clearly, the gas sensitivity of the sensor increases with increasing Pd@Pt loading. However, the sensing performance of 0.5 wt% Pd@Pt-ZnO decreased, likely due to agglomeration caused by excessive Pd@Pt.
[0028] Figure 5 (a)-(f) show the dynamic response curves of 0.1wt% Pd@Pt-ZnO, 0.3wt% Pd@Pt-ZnO, 0.5wt% Pd@Pt-ZnO, ZnO, 0.3wt% Pd-ZnO, and 0.3wt% Pt-ZnO to nitrogen dioxide from 300ppt to 100ppb at their respective optimal operating temperatures.
[0029] like Figure 5 As shown, the dynamic response of the six sensors to nitrogen dioxide concentrations ranging from 300 ppt to 100 ppt is evident at their respective optimal operating temperatures. The response gradually increases with increasing concentration. The 0.3 wt% Pd@Pt-ZnO material exhibits a response value of 1.2 at 80°C for nitrogen dioxide concentrations as low as 300 ppt. The response values of the other five sensors for this concentration are all less than 1.2, demonstrating the sensor's potential for application in the detection of low-concentration nitrogen dioxide.
[0030] Figure 6 (a) and (b) are the response recovery curves of 0.3wt% Pd@Pt-ZnO and pure ZnO materials to 50ppb nitrogen dioxide at 80℃.
[0031] like Figure 6 As shown, the response recovery time of the material was reduced by 49 seconds and 231 seconds after loading Pd@Pt nanocrystals, respectively, demonstrating the strong catalytic activity of Pd@Pt nanocrystals.
[0032] Figure 7 Repeatability curves of 0.3wt% Pd@Pt-ZnO at 80℃ for 50ppb nitrogen dioxide.
[0033] like Figure 7 As shown, the device exhibits good repeatability.
[0034] Figure 8 Bar graphs showing the selectivity of ZnO, 0.3wt% Pd-ZnO, 0.3wt% Pt-ZnO, 0.1wt% Pd@Pt-ZnO, 0.3wt% Pd@Pt-ZnO, and 0.5wt% Pd@Pt-ZnO for 50 ppb nitrogen dioxide and 100 ppm other gases at their respective optimal operating temperatures.
[0035] like Figure 8 As shown, the composite material loaded with Pd@Pt nanocrystals exhibits excellent selectivity. Among them, 0.3wt% Pd@Pt-ZnO has a much higher response to gases than other materials, and its response to 50ppb nitrogen dioxide is more than 30 times that of other interfering gases, demonstrating its good selectivity. Detailed Implementation
[0036] Example 1:
[0037] (1) Dissolve 5.94 g of zinc nitrate hexahydrate and 0.174 g of sodium dodecylbenzenesulfonate in 40 mL of deionized water and stir thoroughly until dissolved to obtain solution A. Then dissolve 2.4 g of sodium hydroxide in 15 mL of deionized water, add the prepared sodium hydroxide aqueous solution dropwise to solution A and stir for 30 min. Transfer the resulting mixture to an autoclave and heat at 90 °C for 2 hours. After naturally cooling to room temperature, wash the precipitate four times with deionized water and ethanol, and collect it. Dry the product at 60 °C overnight and then calcine at 400 °C for 2 hours to obtain ZnO nanosheets with a mass of 3.28 g.
[0038] (2) Dissolve 50 mg of polyvinylpyrrolidone, 50 mg of ascorbic acid, 0.1 mmol of sodium tetrachloropalladium, and 0.1 mmol of platinum acetylacetonate in 10 mL of ethylene glycol. Stir thoroughly until completely dissolved, then heat to 180 °C in an oil bath and maintain for 3 hours. After cooling to room temperature, wash the resulting precipitate four times by centrifugation with acetone and ethanol, and collect the precipitate. Disperse the product in 10 mL of ethanol to obtain a bimetallic Pd@Pt nanocrystal ethanol dispersion. Then measure its concentration: weigh the small glass slide on a balance; use a pipette to take 20 μL of the Pd@Pt ethanol dispersion, drop it onto the glass slide, wait for the ethanol to evaporate, and weigh it again. The mass is 0.03 mg. Repeat several times and take the average value to obtain the concentration of Pd@Pt dispersion as 1.5 mg / mL.
[0039] (3) 100 mg of ZnO nanosheets obtained in step (1) were ultrasonically dispersed in 10 mL of ethanol, and 0.2 mL of the ethanol dispersion of bimetallic Pd@Pt nanocrystals obtained in step (2) was added to it. The mixture was stirred for 30 minutes. The amount of bimetallic Pd@Pt nanocrystals was 0.3% of the mass of ZnO nanosheets. Finally, the mixture was dried overnight in an oven at 60 °C to obtain a core-shell structured bimetallic Pd@Pt nanocrystal modified ZnO sensitive material (labeled as 0.3 wt% Pd@Pt-ZnO) with a product mass of 100.03 mg.
[0040] (4) Mix 10 mg of Pd@Pt nanocrystal modified ZnO sensitive material with 1 mL of ethanol in a mortar. Then, use a small brush to evenly coat the mixture onto the outer surface of an alumina ceramic tube with a length of 4 mm, an outer diameter of 1.2 mm, and an inner diameter of 0.8 mm, and cover it with a gold electrode to form a 15 μm thick sensitive material film. Then, bake the alumina ceramic tube with Pd@Pt nanocrystal modified ZnO material under an infrared lamp for 10 minutes. After the ethanol evaporates, sinter the alumina ceramic tube in a muffle furnace at 300 °C for 2 h to improve its mechanical strength.
[0041] (5) The sintered ceramic tube is welded onto a hexagonal base, and a nickel-chromium heating wire (resistance value of 30 ohms) is inserted into the ceramic tube as a heater. The operating temperature of the device is controlled by adjusting the current. The device is aged at 200℃ for 5 days to obtain a nitrogen dioxide gas sensor with a low detection limit based on a core-shell bimetallic Pd@Pt nanocrystal modified ZnO.
[0042] Example 2:
[0043] ZnO nanosheets and Pd@Pt nanocrystal ethanol dispersions were prepared according to the method in Example 1, with the mixing ratio of the two varied. 0.067 mL of the Pd@Pt ethanol dispersion was mixed with 10 mL of an ethanol solution containing 100 mg of ZnO nanosheets. The resulting device contained 0.1% Pd@Pt by mass of ZnO and was labeled as 0.1 wt% Pd@Pt-ZnO. The device fabrication and testing methods were consistent with those in Example 1.
[0044] Example 3:
[0045] ZnO nanosheets and Pd@Pt nanocrystal ethanol dispersions were prepared according to the method in Example 1, with the mixing ratio of the two varied. 0.33 mL of the Pd@Pt ethanol dispersion was mixed with 10 mL of an ethanol solution containing 100 mg of ZnO nanosheets. The resulting device contained 0.5% Pd@Pt by mass of ZnO and was labeled as 0.5 wt% Pd@Pt-ZnO. The device fabrication and testing methods were consistent with those in Example 1.
[0046] Comparative Example 1:
[0047] ZnO nanosheets were prepared according to the method in Example 1. Pd nanocrystals were prepared using a similar method to Example 1, but without the addition of platinum acetylacetone solution. 0.5 mL of an ethanol dispersion of Pd nanocrystals was mixed with 10 mL of an ethanol solution containing 100 mg of ZnO nanosheets. The resulting device contained 0.3% Pd by mass of ZnO and was labeled as 0.3 wt% Pd-ZnO. The device preparation and testing methods were consistent with those in Example 1. Comparative Example 2:
[0048] ZnO nanosheets were prepared according to the method in Example 1. Pt nanocrystals were prepared using a similar method to Example 1, but without the addition of sodium tetrachloropalladium solution. 0.6 mL of an ethanol dispersion of Pt nanocrystals was mixed with 10 mL of an ethanol solution containing 100 mg ZnO. The resulting device contained 0.3% Pt by mass of ZnO and was labeled as 0.3 wt% Pt-ZnO. The device preparation and testing methods were consistent with those in Example 1.
[0049] Comparative Example 3:
[0050] Pure-phase ZnO nanosheets were prepared according to the aforementioned method. 10 mg of ZnO nanosheets and 1 mL of ethanol were mixed evenly in a mortar. Then, the mixture was evenly coated on the outer surface of an alumina ceramic tube with a length of 4 mm, an outer diameter of 1.2 mm, and an inner diameter of 0.8 mm with a small brush and covered with gold electrodes. The remaining steps were the same as in Example 1.
Claims
1. A nitrogen dioxide gas sensor based on a core-shell bimetallic Pd@Pt nanocrystal-modified ZnO, comprising an alumina ceramic tube substrate with two annular gold electrodes on its outer surface, a sensitive material coated on the gold electrodes and the outer surface of the alumina ceramic tube, and a nickel-chromium heating wire located inside the alumina ceramic tube substrate, characterized in that: The sensitive material is ZnO modified with core-shell bimetallic Pd@Pt nanocrystals, and it is prepared by the following steps. (1) Dissolve 5.8-6.2g of zinc nitrate hexahydrate and 0.16-0.18g of sodium dodecylbenzenesulfonate in 30-50mL of deionized water and stir thoroughly until dissolved to obtain solution A; then dissolve 2.2-2.6g of sodium hydroxide in 10-20mL of deionized water, add the obtained sodium hydroxide aqueous solution dropwise to solution A and stir for 20-40min; transfer the resulting mixture to an autoclave and heat at 80-100℃ for 1.5-2.5 hours; after naturally cooling to room temperature, wash the obtained precipitate by centrifugation with deionized water and ethanol 3-6 times in sequence and collect it; dry the obtained product at 50-70℃ overnight, and then calcine at 350-450℃ for 0.5-2.0 hours to obtain ZnO nanosheets; (2) Dissolve 40-60 mg of polyvinylpyrrolidone, 40-60 mg of ascorbic acid, 0.05-0.15 mmol of sodium tetrachloropalladium and 0.05-0.15 mmol of platinum acetylacetonate in 8-12 mL of ethylene glycol and stir thoroughly until completely dissolved. Then heat in an oil bath to 160-200 °C and maintain for 2-5 hours. After cooling to room temperature, wash the precipitate with acetone and ethanol by centrifugation 3-6 times in sequence and collect it. Disperse the product in ethanol to obtain a bimetallic Pd@Pt nanocrystal ethanol dispersion. (3) 100 mg of ZnO nanosheets obtained in step (1) were ultrasonically dispersed in 8-12 mL of ethanol, and the ethanol dispersion of Pd@Pt nanocrystals obtained in step (2) was added to it. The mixture was stirred for 20-40 minutes. The amount of bimetallic Pd@Pt nanocrystals was 0.1-0.5% of the mass of ZnO nanosheets. Finally, the mixture was dried overnight at 50-70 °C to obtain a core-shell structured bimetallic Pd@Pt nanocrystal modified ZnO sensitive material.
2. The method for preparing a nitrogen dioxide gas sensor based on core-shell bimetallic Pd@Pt nanocrystals modified with ZnO as described in claim 1, comprising the following steps: ① Mix 10-20 mg of core-shell bimetallic Pd@Pt nanocrystal modified ZnO sensing material with 1-3 mL of ethanol in a mortar until homogeneous. Then, uniformly coat the resulting mixture onto the outer surface of an alumina ceramic tube and cover it with a gold electrode to form a 12-16 μm thick sensing material film. Bake under an infrared lamp for 8-15 minutes. After the ethanol evaporates, sinter the alumina ceramic tube at 250-350 °C for 1.5-3.0 h to improve the mechanical strength of the sensing material. ② The sintered alumina ceramic tube is welded onto a hexagonal base, and a nickel-chromium heating wire is inserted inside the alumina ceramic tube as a heater to control the working temperature of the sensor. The tube is aged at 180-220°C for 3-6 days to obtain the low detection limit nitrogen dioxide sensor based on core-shell bimetallic Pd@Pt nanocrystal modified ZnO as described in this invention.
Citation Information
Patent Citations
Single-layer and multi-layer hollow carbon nanosphere and preparation method and application thereof
CN104843665A
Perovskite quantum dot material with gas-sensitive property and application thereof
CN114540024A